Current Challenges Of The Globalization Process (2016)
This book discusses the main challenges of the globalization process nowadays, concerning the adjustments to the neoliberal economic model due to the negative effects of financial crises, the development goals for the next fifteen years, the transcendental technological changes, their implications in the development of cognitive capitalism, the difficult task of facing the consequences of global warming, the implications of the prevalence of human rights over the rights of nations, and the possibilities of emerging nations in the redistribution of world power in an environment altered by the presenceof fundamentalist groups. These challenges suggest the relevance of a globalizing process that, given the time elapsed, deserves changes worldwide.